Current Tobacco Use Among Adults in the United States: Findings From the National Adult Tobacco Survey - King, Brian A. (American Public Health Association, 2012)
Objectives. We assessed the prevalence and sociodemographic correlates of tobacco use among US adults. Methods. We used data from the 2009–2010 National Adult Tobacco Survey, a national landline and cell phone survey of adults aged 18 years and older, to estimate current use of any tobacco; cigarettes; cigars, cigarillos, or small cigars; chewing tobacco, snuff, or dip; water pipes; snus; and pipes. We stratified estimates by gender, age, race/ethnicity, education, income, sexual orientation, and US state. Results. National prevalence of current use was 25.2% for any tobacco; 19.5% for cigarettes; 6.6% for cigars, cigarillos, or small cigars; 3.4% for chewing tobacco, snuff, or dip; 1.5% for water pipes; 1.4% for snus; and 1.1% for pipes. Tobacco use was greatest among respondents who were male, younger, of non-Hispanic “other” race/ethnicity, less educated, less wealthy, and lesbian, gay, bisexual, or transgender. Prevalence ranged from 14.1% (Utah) to 37.4% (Kentucky). Conclusions. Tobacco use varies by geography and sociodemographic factors, but remains prevalent among US adults. Evidence-based prevention strategies are needed to decrease tobacco use and the health and economic burden of tobacco-related diseases.